Factors influencing methane-derived authigenic carbonate formation at cold seep from southwestern Dongsha area in the northern South China Sea - Wang, Shuhong
This paper carried out mineral and geochemical studies on a proﬁle through a diagenetic methane-derived authigenic carbonate sample that was collected from southwestern Dongsha area of the northern South China Sea. Five samples locating in the cross-sectional middle mainly consist of dolomite and quartz, and two samples close to the surface have a small amount of Mg-calcite. The d13C values of the samples vary between -30.59 and -0.30 % VPDB, with d18O values ranging from 3.07 to 3.59 % VPDB, d44/40Ca values ranging from 1.35 to 1.47 % SRM915a, indicating a contribution of methane to the carbon pool where the precipitation of authigenic carbonates occurred. Based on the isotope values alone, it can not be distinguished if the carbon source is thermogenic gas or a mixture of biogenic methane and marine dissolved inorganic carbon. The d18O values are in general consistent with dolomite precipitation from a ﬂuid similar to present seawater. The observed small variation might be related to the oxygen isotope composition of seep ﬂuid. The relative small range in calcium isotope values suggests that relatively constant growth conditions and precipitation from seawater. The central part of the carbonate nodule formed under the strong inﬂuence of methane seepage, and the external part is less inﬂuenced by methane, either due to reduced methane ﬂux to the surface or caused by erosional exhumation of the carbonate nodule from greater depth to the sediment surface.